2023
DOI: 10.3389/fvets.2022.1083842
|View full text |Cite
|
Sign up to set email alerts
|

Effect of purple corn extract on performance, antioxidant activity, egg quality, egg amino acid, and fatty acid profiles of laying hen

Abstract: The objective of this study was to investigate the effects of anthocyanin-rich purple corn extract (PCE) on performance, antioxidant potential, egg quality, egg amino acid and fatty acid profiles of laying hens during the late laying period. A total of 360 88-wk-old laying hens were randomly divided into 4 groups, and fed a basal diet (CON) or a basal diet supplemented with 120 (LP), 240 (MP), and 360 mg/kg (HP) PCE, respectively. No significant difference (P > 0.05) was observed in the ADFI or average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…This suggests that further work is still needed to evaluate the specific mechanism of honeycomb extracts to ascertain their efficacy. Our observations were consistent with Li et al ( 53 ), who found that feeding of anthocyanins from purple corn extract could improve flavor amino acids content in eggs compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that further work is still needed to evaluate the specific mechanism of honeycomb extracts to ascertain their efficacy. Our observations were consistent with Li et al ( 53 ), who found that feeding of anthocyanins from purple corn extract could improve flavor amino acids content in eggs compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…The addition of FAMP had no significant impact on most of the amino acid composition of egg albumen ( Table 4 ). In contrast, a diet supplemented with 120–360 mg/kg anthocyanin-rich purple corn extract could improve most EAA and NEAA concentrations in eggs (Li J. et al, 2023 ). This disagreement is possibly influenced by the differences in feed composition, breeds, and ages of laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary 2.5% AMP increased tocopherol content and exhibited better antioxidant properties in egg yolk (Loetscher et al, 2014 ). Polyphenol-rich additives like AMP, Aronia melanocarpa (Jing et al, 2022 ), grape pomace (Reis et al, 2019 ), and purple corn extract fed to laying hens (Li J. et al, 2023 ) improved ovary or plasma antioxidant capacity via regulating the Keap1/Nrf2 signaling pathway, which is responsible for xenobiotic and oxidant elimination (Bhattacharyya et al, 2014 ). Nrf2 regulates defensive gene expression concerning antioxidant proteins, such as HO-1, GPX1, SOD1, and SOD2, which exert antioxidant effects (Tonelli et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although these authors assumed that anthocyanins or other compounds might be responsible for decreasing egg weight, recent studies contradict them. Anthocyanins rich diets, supplemented with chokeberry, black currant, and raspberry ( Sosnówka-Czajka and Skomorucha, 2021 ) or 200 and 400 mg/kg anthocyanin-rich roselle ( Li et al, 2023 ) had no detrimental effect on egg characteristics during long term feeding (20 wk) of Hy-Line commercial hybrid laying hens at peak production (42 wk old) or late laying phase (88 wk old) Chishui black-bone hen. Further, the significant changes in albumen, yolk, and yolk/albumen ratio, are directly correlated with the modifications of egg and yolk weight.…”
Section: Discussionmentioning
confidence: 99%